Pengaruh Lingkungan Kerja, Budaya Organisasi, Kepemimpinan Terhadap Kinerja Karyawan - Mohamad Rafli Saputra; Suhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to assess the influence of the work environment, organizational culture and leadership on employee performance. The research was conducted at PT. INNAN with permanent employees as a sample. Factor analysis is used to test the validity of research data. SPSS software version 27.0 was used by researchers for data analysis. The research results show that the work environment has a significant effect on employee performance. Organizational culture has a significant effect on employee performance and leadership has an effect on employee performance. This research provides input for companies theoretically and practically.